Analisis Pengupahan terhadap Sistem Upah Kerja Borongan Buruh Bangunan Berdasarkan Fatwa DSN MUI Nomor 09/DSN-MUI/VI/2000 dan Peraturan Pemerintah Nomor 36 Tahun 2021 - Nur Alvi Maulidi Hidayah; Ira Siti Rohmah Maulida; Asep Ramdan Hidayat (Bandung Conference Series: Sharia Economic Law, 2023)
Wages are an important component of the relationship between companies and their workers. Researchers analyzed wage practices carried out by PT. Raytama Bintang Arbani where the company is one of the companies in the construction sector that uses the services of workers/laborers who work according to what the company expects. The rampant remuneration is arbitrary because it is caused by the ignorance of both parties about the wage system. Researchers use the theories of wages that exist in the Fatwa regarding ijarah, and Government Regulations regarding wages. The purpose of this study is to find out and explain the practice of giving wages to construction workers at PT. Raytama Bintang Arbani. Second, to find out and explain the analysis of Islamic law on the practice of wages for construction workers at PT. Raytama Bintang Arbani. The researcher analyzed using Fatwa No. 09 of 2000 concerning ijarah contracts and also Government Regulation Number 36 of 2021 concerning Wages. The method used in this research is qualitative research, a type of research that describes systematically what is happening in the field. The data collection techniques used in this study are observation, interviews, and documentation. Based on the results of research in the field, it is true that at PT. Raytama Bintang Arbani under this contract labor wage system, the standard wages given to workers are not the same value as the same work because wages are also based on the length of work of workers/laborers at PT. Raytama Bintang Arbani. The amount of wages, which also has a value, has been determined by the company, so workers cannot negotiate, for fear of losing their jobs. The average worker in this company has a low level of education, so they don't understand regulations. Companies should be wiser and understand wage regulations.